MODERN APPROACHES TO LABORATORY DIAGNOSIS OF EPILEPSY: CURRENT METHODS AND THEIR SIGNIFICANCE - Turdiyeva Dildora Shavkatovna; Yulayeva Irina Andreevna; Isomadinova Lola Kamolidinovna (Web of Journals Publishing, 2024)
Epilepsy is a chronic neurological disease characterized by various subtypes and a variety of painful manifestations, which often complicate accurate diagnosis and effective treatment. Laboratory methods, such as molecular genetic testing, biochemical blood analysis, the study of biomarkers and new therapeutic targets, make it possible to clarify the diagnosis, differentiate subtypes of epilepsy and adaptive therapy for each patient.This article describes the latest laboratory methods and their clinical significance, including the occurrence of genetic mutations, monitoring of antiepileptic drugs and metabolic analysis, which gives a new look at the pathogenesis and prognosis of the course of epilepsy.
Keywords: epilepsy, laboratory diagnostics, genetic development, biomarkers, antiepileptic drugs, metabolomics, neuroinflammation, pathogenesis of epilepsy.